1965
DOI: 10.1039/an9659000649
|View full text |Cite
|
Sign up to set email alerts
|

The identification and determination of chlorinated pesticides residues

Abstract: Gasliquid chromatography provides a method of extreme sensitivity for the detection and determination of organochlorine pesticides residues. A single retention-time cannot, however, be regarded as a reliable identification of an unknown compound. A "clean-up" procedure is described by which interference is virtually eliminated, and a technique is proposed in which the change in retention-time after simple chemical reactions provides confirmation of the identity of a pesticide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1969
1969
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In ourgaschromatographicprocedures-as in many others-these products gave peaks with retention times similar to DDT-isomers and metabolites, as can be seen in Figure 1. We therefore applied two transformation reactions in parallel: The alkali treatment causes dehydrochlorination of the DDT-isomers as follows [5,6]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ourgaschromatographicprocedures-as in many others-these products gave peaks with retention times similar to DDT-isomers and metabolites, as can be seen in Figure 1. We therefore applied two transformation reactions in parallel: The alkali treatment causes dehydrochlorination of the DDT-isomers as follows [5,6]:…”
Section: Resultsmentioning
confidence: 99%
“…In ourgaschromatographicprocedures-as in many others-these products gave peaks with retention times similar to DDT-isomers and metabolites, as can be seen in Figure 1. We therefore applied two transformation reactions in parallel: The alkali treatment causes dehydrochlorination of the DDT-isomers as follows [5,6] If present, less frequently encountered compounds, such as methoxychlor, perthane, and o,p'-TDE, are also converted to their respective olefins. All dehydrochlorinations occur with a yield of 93-100% [7,8].…”
Section: Resultsmentioning
confidence: 99%
“…One method which can be useful in such cases is observation of the changes in the gas chromatogram after some (preferably simple) chemical or physical treatment (Asai et al, 1967;Banks and Bills, 1968;Cochrane, 1968, 1969a, b;Chau, 1969;Cochrane, 1969;Hamence et al, 1965;Kawano et al, 1969;McCully, 1969;Pionke et al, 1969;Wiencke and Burke, 1969). In the course of our investigations on the occurrence of endosulfan in surface waters (notably the river Rhine) we found that observation of the glc peak shifts under the influence of diluted ethanolic alkali can provide useful additional evidence for the presence of that insecticide.…”
mentioning
confidence: 96%
“…Chemical derivatization is a more specific way of comparing unknown and reference material and a number of chlorinated pesticides have been identified by derivatization (2)(3)(4). However, each derivative formed is a product of specific chemical reaction and only a few pesticides can be determined by any one procedure.…”
mentioning
confidence: 99%